Palliative Interventional Oncology. Issue 6 (November 2016) - Fairchild, Alexandra H.; Rilling, William S.
Abstract : Abstract: Interventional oncologists are playing an ever greater role in improving the quality of life of their patients through minimally invasive procedures, many of which can be performed on an outpatient basis. Some of the most common palliative procedures currently performed will be discussed including management of intractable ascites and pleural effusions, neurolytic plexus blocks, and palliation of pain and bleeding associated with metastatic tumors.